Bedhayan Gagrag Sumirat Puspito dance: The innovation in conveying Islamic da’wah through arts - Restian, Arina Restian; Jazuli, Muhammad; Cahyono, Agus; Yanuartuti, Setyo (Research Journal in Advanced Humanities, 2024)
The development of Islam in Indonesia has been affected by Islamic organizations that use cultural acculturation to integrate local traditions into religious practices. Muhammadiyah, which is active in social and educational initiatives, integrates traditional arts such as dance to subtly spread Islamic values, represented by Bedhayan Gagrag Sumirat. This integration enriches cultural heritage while promoting religious teachings, serving as a form of da’wah among the Indonesian Muslim community. The aim of this research is to study social phenomena in society regarding the cultural acculturation of Yogyakarta and Malang through the Bedhayan Gagarag Sumirat dance which is integrated with Muhammadiyah Islam. This research was conducted qualitative approach using observations and interviews. The research results in the process of the Bedhayan Gagrag Sumirat Dance are a form of cultural acculturation of Yogyakarta and Malang with integrated Muhammadiyah Islamic values. The Bedhayan Gagrag Sumirat dance not only depicts the richness of local culture, but also teaches Muhammadiyah Islamic values. As an innovative and effective means of preaching, this modern dance reflects local cultural harmony and conveys religious messages through art.